The future incidence of leprosy: a scenario analysis - Meima Abraham; Smith W. Cairns S.; van Oortmarssen Gerrit J.; Richardus Jan H.; Habbema J. Dik F. (The World Health Organization, 2004)
OBJECTIVE: To investigate the impact of the current strategy for the elimination of leprosy on its incidence and to assess the consequences of failure to sustain this strategy. METHODS: Scenarios for assessing the impact of the elimination strategy were implemented in a computer simulation program. The scenarios reflected the assumptions made regarding contagiousness, transmission and bacille Calmette-Guérin (BCG) vaccination. The trend in case detection rate for the main countries in which leprosy was endemic during 1985-98 was fitted, and incidence up to 2020 was projected. FINDINGS: Owing to the gradual shortening of delays in detection up to 1998, and because of the low relapse rate that occurs with multidrug treatment MDT, incidence is predicted to decrease beyond 2000 in all scenarios. The annual decline was a few per cent higher when favourable assumptions were made about protection and coverage of BCG vaccination. Overall, the predicted annual decline in incidences ranged from 2% to 12%. CONCLUSION: The elimination strategy reduces transmission, but the decline may be slow. Relaxation of control after 2005 is unjustified given the uncertainty about the rate of decline and the adverse effects of longer delays in detection. A long-term strategy for leprosy control should be adopted.